Metabolic/bariatric surgery optimization: a position statement by Arabic association for the study of diabetes and metabolism (AASD) - Amin Roshdy Soliman; Hesham Magd eldin Saleem; Amr Abel Hady El Meligi; Mervat Naguib; Rasha Sobh Mohamed; Ghada Rabie Abdelaziz; Maha Rakha; Shereen Abdelghaffar; Abd ElKhalek Hamed; Hany Abd El Rahman saeed Hammad; Eman O Mahmoud; Inass Shaltout (Diabetology & Metabolic Syndrome)
Abstract For patients considering bariatric surgery, it is essential to have clear answers to common questions to ensure the success of the procedure. Patients should understand that surgery is not a quick fix but a tool that must be complemented by lifestyle changes, including dietary adjustments and regular physical activity. The procedure carries potential risks that should be weighed against the potential benefits. Health authorities play a critical role in ensuring that bariatric surgery is performed under the highest standards of care. Recommendations are provided to determine who is an appropriate candidate for surgery, what preoperative evaluations are necessary, and how to monitor patients postoperatively to maximize outcomes and minimize risks. Additionally, authorities are responsible for ensuring access to follow-up care, including nutritional support and psychological counseling, which are vital for the long-term success of bariatric surgery. Understanding these aspects by both patients and decision-makers is critical before proceeding with bariatric surgery. The following questions guide patients and healthcare professionals in making informed decisions about the procedure and managing the expectations and outcomes associated with bariatric surgery.